Market competition for high‐density residential land - Cypher, Matthew L.; Hayunga, Darren K. (International Journal of Strategic Property Management, 2010)
We investigate the potential competition between multifamily and condominium developers for raw land throughout the U.S. When considering the entire sample period, we find evidence that condominium developers paid, on average, more for land than their multifamily counterparts. Alternatively, when we separate the sample into low versus high‐growth locations and two time subperiods, we observe that the premium is not entirely consistent. The average premiums appear to be largely a result of the high‐growth locations from 2004 to mid‐2008. Indeed, the results demonstrate that condominium developers paid over 60 percent more for land in high‐growth states during the later subperiod. This extraordinary premium calls into question the price formation process in these locations.First Published Online: 18 Oct 2010